ANALISIS PROPAGASI PADA KAWASAN KAMPUS UNIVERSITAS NUSA CENDANA PENFUI KUPANG - Leonardo F. Lay; Kalvein Rantelobo; Beby H. A. Manafe (Jurnal Media Elektro, 2019)
In a telecommunications system, a radio propagation model is needed to do a design, construction, and development of mobile communication systems. Propagation models commonly used are the Okumura-Hatta model and the COST model 231. These models are used to determine an accurate propagation model in a particular area. This study aims to obtain a propagation model on the environmental conditions of dry-land such as the University of Nusa Cendana areas by using Okumura-Hata path loss modeling and COST-231. In this study, the acceptance test drive was carried out at frequencies of 900 Mhz, 1800 Mhz and 1900 MHz using the G-NetTrack application on Telkomsel BTS in the University of Nusa Cendana area with Latitude coordinates -10.156738 and Longitude 123.668422 as well as observing frequencies using Spectrum Analyzer to be used as primary data. The next step is to calculate the received power data as secondary data using the Okumura-Hata path loss calculation and COST-231. Based on primary and secondary data an analysis of which propagation model matches the measurements in the field is carried out. From the propagation analysis, it can be concluded that the propagation model that suits the conditions on the campus area is the Okumura-Hatta model.